Unusual case of isolated major aortopulmonary collateral artery perfusing entire functional left lower lobe of the lung - Kyle W Riggs; SiddharthMahajan; DipakKholwadwala; DavidMeyer; Vincent A Parnel (Wolters Kluwer Medknow Publications, 2021)
Pulmonary sequestrations are nonfunctioning pulmonary parenchyma supplied by a systemic artery. We describe an 18-month-old baby girl with no significant past medical history who was found to have a large isolated collateral from the aorta entirely perfusing the functional left lower lobe. Cardiac catheterization confirmed the major aortopulmonary collateral artery supplying the left lower lobe with normal drainage into the left atrium. At a multidisciplinary meeting, decision was made to preserve the functional lobe. During surgery, the collateral artery was dissected and its course within the pleural space appreciated, the main left pulmonary artery was isolated. Intraoperatively surgeons anastomosed an 8 mm ringed conduit from the left pulmonary artery, anteriorly to the proximal aspect of the collateral. The patient tolerated the surgery well. Postoperative echocardiogram showed pulmonary flow to the lower lobe, and she was discharged home on postoperative day 2 without complications.